Mongolia : Fifth and Sixth Reviews under the Stand-By Arrangement and Rephasing of Purchases. (IMF Staff Country Reports; Country Report, 2010)
Despite the negative impact of the severe winter on agriculture, other indicators are pointing to a strong recovery. Exports are growing rapidly, fueled by the rebound in copper prices and a rapid growth in coal exports. Rephasing of purchases by combining the fifth and sixth reviews is requested owing to the delay in completing the fifth review, and earlier-than-planned Board discussion of the sixth review. The sixth review is the final review. The fiscal responsibility law will help secure a lasting fiscal discipline.